A method for preparing 2,5-furandicarboxylic acid using 5-chloromethylfurfural

CN122999254APending Publication Date: 2026-10-30XIAMEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611311432.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但HMF制备成本较高,主要以果糖制备,无法从生物质原料直接获得,且HMF活泼的化学性质和亲水性导致了后续分离提纯难度大,进一步限制了以HMF为原料规模化制备2,5-呋喃二甲酸的进程

Benefits of technology

[0031]本发明所用的原料5-氯甲基糠醛可以直接从纤维素或生物质原料高产率制备,且便于分离提纯,大大降低了原料生产成本,本发明提供一条利用可再生资源制备2,5-呋喃二甲酸的可持续发展路径;本发明所用的催化反应体系,在较温和条件下可以实现原料5-氯甲基糠醛高效转化为2,5-呋喃二甲酸,且所用催化剂易于制备,碱中和剂廉价易得。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application belongs to the field of organic synthesis and provides a method for effectively catalyzing 5-chloromethylfurfural to prepare 2,5-furan dicarboxylic acid by using a carbon-doped N-supported monatomic cobalt catalyst (Co-N-C). The application provides a sustainable development path for preparing 2,5-furan dicarboxylic acid by using renewable resources; under relatively mild conditions, the raw material 5-chloromethylfurfural can be efficiently converted into 2,5-furan dicarboxylic acid, and the catalyst used is easy to prepare, and the base neutralizing agent is cheap and easy to obtain. The problems of high preparation cost, great difficulty in subsequent separation and purification and the like in the traditional process are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic synthesis, specifically relating to a method for preparing 2,5-furandicarboxylic acid using 5-chloromethylfurfural. Background Technology

[0002] 2,5-Furandicarboxylic acid (FDCA) is a promising biomass-derived platform chemical, considered a key "platform compound" connecting renewable biomass resources with future sustainable materials. As an ideal bio-based alternative to petroleum-based terephthalic acid (PTA), it can be used to synthesize a range of high-performance, environmentally friendly polymers and chemicals, such as PEF plastics, nylon / polyurethane, and environmentally friendly plasticizers.

[0003] Generally, 2,5-furandicarboxylic acid (FDCA) can be prepared by catalytic oxidation of biomass-derived furan compounds (such as 5-hydroxymethylfurfural (HMF)). However, HMF preparation is costly, mainly based on fructose, and cannot be obtained directly from biomass feedstocks. Furthermore, the reactive chemical properties and hydrophilicity of HMF make subsequent separation and purification difficult, further limiting the large-scale preparation of 2,5-furandicarboxylic acid using HMF as a raw material.

[0004] 5-Chloromethylfurfural (CMF) is a novel biomass-based platform molecule with a similar molecular structure to HMF. It can be prepared directly from raw materials such as cellulose and biomass in high yield under mild conditions. Its stability and hydrophobicity make it easier to separate and purify in the subsequent process (ACS Sustain. Chem. Eng., 2019, 7(6), 5588-601). However, there is currently a lack of reports on the synthesis of 2,5-furandicarboxylic acid from CMF. Summary of the Invention

[0005] To address the aforementioned problems, this invention provides a method for efficiently catalyzing the preparation of 2,5-furandicarboxylic acid from 5-chloromethylfurfural using a carbon-doped N-supported single-atom cobalt catalyst (Co-NC).

[0006] The catalyst prepared in this invention is a carbon-doped N-supported Co metal single-atom catalyst (denoted as Co-NC), wherein the loading amount of Co is selected to be 1-5%.

[0007] When the loading is below 1%, there are too few Co single-atom sites per unit mass of catalyst, resulting in insufficient overall catalytic activity. Above 5%, Co atoms easily aggregate to form nanoparticles or clusters, disrupting the "single-atom" dispersion and reducing atom utilization. During the conversion of CMF to HMF, HCl is generated. HCl corrodes most catalyst supports, causing structural collapse. Using carbon spheres as a support avoids this corrosion. Furthermore, ordinary oxide catalysts are also corroded by HCl, losing active sites and preventing the reaction from proceeding. The Co-NC single-atom catalyst of this patent exhibits strong acid and corrosion resistance and high stability.

[0008] The preparation method of the Co-NC catalyst includes the following steps:

[0009] (1) Dissolve cobalt acetate tetrahydrate and 1,10-phenanthroline in ethanol and stir until homogeneous;

[0010] (2) Add the carbon support to the solution from step (1) and continue stirring;

[0011] (3) Add nitrogen carbide to the mixture in step (2) and heat while stirring until the ethanol is completely evaporated;

[0012] (4) Calcine the solid dried in step (3);

[0013] (5) The black solid after calcination is acid-washed, water-washed and dried to obtain Co-NC catalyst.

[0014] Preferably, in step (1), the mass ratio of cobalt acetate tetrahydrate to 1,10-phenanthroline is 1:1-1:5; the stirring time is 20-60 min. Cobalt acetate tetrahydrate is readily soluble in ethanol, facilitating uniform mixing with nitrogen-containing ligands. 1,10-phenanthroline has strong chelating ability and can bind with Co... 2+ Forming stable complexes to prevent Co 2+ Aggregation occurs before pyrolysis. A mass ratio of 1:1 to 1:5 is selected to ensure Co... 2+ Complete coordination, increasing the ratio to 1:5, can further inhibit Co at high concentrations. 2+ If the aggregation ratio is too high (e.g., >1:6), a thick carbon layer may form after pyrolysis, hindering the reactants from approaching the Co active sites. 2+ Coordination with 1,10-phenanthroline is relatively rapid at room temperature (typically forming a colored complex within minutes). However, to obtain a homogeneous solution or suspension, 20–60 minutes is sufficient for molecular-level mixing, with 30 minutes being the optimal choice.

[0015] As a preferred option, in step (1), the mass ratio of cobalt acetate tetrahydrate to 1,10-phenanthroline is further preferred to be 1:1.5-1:2, with the optimal choice being 1:1.75.

[0016] Preferably, in step (2), the stirring time is 0.5-3h, preferably 1h.

[0017] Preferably, in step (3), the mass ratio of nitrogen carbide to carbon support is 3:1-1:3; nitrogen carbide is chosen because it has a high nitrogen content, and thermal decomposition releases a large number of nitrogen free radicals, which are efficiently doped into the carbon support to form abundant Co-N. x Coordination sites. A mass ratio of 3:1 to 1:3 is selected to ensure sufficient nitrogen doping, but if the ratio is too high, nitrogen carbide will encapsulate Co nanoparticles during pyrolysis, preventing them from forming stable single atoms. Further optimization is achieved with a nitrogen carbide to carbon support mass ratio of 2:1 to 1:2, with the optimal ratio being 1:1.

[0018] Preferably, in step (3), the ethanol is heated and stirred at a temperature of 50-90°C until it is completely evaporated, preferably at a temperature of 60-70°C until it is completely evaporated, and even more preferably at a temperature of 65°C until it is completely evaporated.

[0019] Preferably, in step (4), the calcination is carried out at 700-1100℃ for 1-4 hours, and more preferably at 900℃ for 2 hours.

[0020] Preferably, step (5) involves stirring the calcined black solid in 6-10M H2SO4 for 10-36 hours, then washing it with water, drying it, and finally obtaining the Co-NC catalyst. Preferably, the calcined solid is stirred in 8M H2SO4 for 24 hours, then washed with water, and dried.

[0021] The present invention also provides a method for preparing 2,5-furandicarboxylic acid using 5-chloromethylfurfural, comprising the following steps:

[0022] 5-Chloromethylfurfural, Co-NC catalyst, base neutralizer and water were added to a reaction vessel, and oxygen was used as the oxygen source to catalyze the synthesis of 2,5-furandicarboxylic acid from 5-chloromethylfurfural.

[0023] Preferably, the mass ratio of 5-chloromethylfurfural (g) to Co-NC catalyst (g) is 1:0.5-1:5; preferably 1:2. When there is less catalyst, the reaction rate is limited by the number of active sites, and the intermediate product cannot be completely converted. When there is too much catalyst, the economy will deteriorate. Therefore, 1:2 is the best ratio.

[0024] Preferably, the mass ratio (g) of 5-chloromethylfurfural to the mass ratio (g) of the alkali neutralizing agent is 1:1 to 1:3; preferably 1:2; the alkali neutralizing agent is one or more of calcium carbonate, magnesium oxide, and sodium bicarbonate; preferably sodium bicarbonate. This is because if the alkali ratio is too low, the intermediate product cannot be converted into FDCA, and the HCl produced during the conversion of CMF to HMF cannot be completely consumed. If the alkali ratio is too high, the solution pH will increase, and the HMF generated by the dechlorination of CMF will polymerize, preventing subsequent reactions from proceeding. Sodium bicarbonate is chosen because its solution pH is relatively low, approximately between 7 and 8. If the solution pH exceeds 9, the HMF generated by the dechlorination of CMF will polymerize.

[0025] Preferably, the ratio of 5-chloromethylfurfural (g) to water (mL) is 1:30-1:250; more preferably 1:50-100. When the substrate concentration is too high, the substrate is prone to polymerization, and excess HCl will affect subsequent reactions. If the substrate concentration is too low, the economic efficiency will be too low. Therefore, a ratio of 1:50-100 is preferred, and at this concentration, the yield of FDCA is relatively high, ensuring both yield and economic efficiency.

[0026] Preferably, the initial oxygen pressure is 0.5-5 MPa; more preferably 0.5-3 MPa; and more preferably 1 MPa.

[0027] Preferably, the reaction temperature is 100-150℃; more preferably 110-130℃; the reaction is carried out at a stirring speed of 600-1000 rpm, preferably 800 rpm.

[0028] Preferably, the reaction time is 0.5-8h; more preferably 1-6h; more preferably 2-5h, and even more preferably 3h.

[0029] This is because excessive oxygen pressure, temperature, and reaction time can lead to over-oxidation of the product, and when these conditions are not met, the intermediate product cannot be completely converted.

[0030] The beneficial effects of this invention are:

[0031] The raw material 5-chloromethylfurfural used in this invention can be directly prepared from cellulose or biomass raw materials in high yield and is easy to separate and purify, which greatly reduces the production cost of raw materials. This invention provides a sustainable development path for the preparation of 2,5-furandicarboxylic acid using renewable resources. The catalytic reaction system used in this invention can achieve efficient conversion of the raw material 5-chloromethylfurfural into 2,5-furandicarboxylic acid under relatively mild conditions, and the catalyst used is easy to prepare and the alkali neutralizing agent is inexpensive and readily available. Attached Figure Description

[0032] Figure 1The image shows the Raman spectra of the catalyst.

[0033] Figure 2 The X-ray diffraction (XRD) pattern of the catalyst;

[0034] Figure 3 The high-resolution N1s X-ray photoelectron spectroscopy (XPS) spectrum of the catalyst. Detailed Implementation

[0035] To more clearly illustrate the purpose, technical solution, and advantages of this invention, a detailed description will be provided below in conjunction with the accompanying drawings and specific embodiments. The drawings illustrate only exemplary embodiments of the invention and are not intended to limit its implementation. This invention can be implemented in various forms, and its design concept and core technology are not limited to the embodiments shown in the drawings. These embodiments are provided to facilitate understanding of the principles, structure, and function of this invention by those skilled in the art, thereby enabling them to better master and apply its technical solutions. The terminology used in this specification is only for describing specific embodiments and does not constitute a limitation of the invention.

[0036] Example 1

[0037] Step (1) Preparation of the catalyst Co-NC:

[0038] 0.229 g of Co(CH3COO)2·4H2O was weighed and dissolved in 30 mL of ethanol. Then, 0.4 g of 1,10-phenanthroline was weighed and added to the solution, and the mixture was stirred for 30 min. Next, 1 g of carbon support was added, and the mixture was stirred for 1 h. Then, 1 g of nitrogen carbide was added, and the mixture was heated to 65 °C and stirred until completely dry. The resulting black solid was calcined at 900 °C for 2 h. The calcined solid was stirred in 8 M H2SO4 for 24 h, washed with water, dried, and separated to obtain the Co-NC catalyst, denoted as Co-NC(2).

[0039] Step (2) Catalytic reaction:

[0040] 10 ml of water was added to a glass bottle and heated to 100 °C. Then, 0.1 g of 5-chloromethylfurfural was added and the bottle was sealed. The mixture was stirred at 350 rpm for 2 min. The solution was then transferred to a sealed stainless steel reactor, and 0.2 g of the catalyst obtained in step (1) and 0.2 g of sodium bicarbonate, a base neutralizer, were added. 1 MPa of O2 was introduced, and the mixture was heated to 120 °C at 800 rpm for 3 h. After the reaction, solid-liquid separation was performed using a centrifuge at 8000 rpm for 5 min. Qualitative and quantitative analysis was performed using HPLC (Water 2487). The results are listed in Table 1, numbered 1.

[0041] The Raman spectrum of the catalyst Co-NC(2) is shown below. Figure 1 X-ray diffraction (XRD) patterns are shown below. Figure 2 The high-resolution N1s X-ray photoelectron spectroscopy (XPS) spectrum is shown below. Figure 3 .

[0042] The test conditions are as follows:

[0043] Liquid chromatograph model: Alliance e2695 (Waters), chromatographic column: Aminex HPX-87H organic acid column, placed in a column oven at 60℃ to maintain constant temperature.

[0044] Mobile phase: The mobile phase used for product detection is a 0.005 M H2SO4 aqueous solution, and the flow rate during the detection process is 0.6 mL / min.

[0045] Detector: The detector used for product detection is a UV-Vis detector. FDCA (2,5-furandicarboxylic acid) and HMFCA (5-hydroxymethyl-2-furandicarboxylic acid) are used at wavelengths... Quantification was performed at 260 nm; while FFCA (5-formyl-2-furanoic acid) and HMF (5-hydroxymethylfurfural) were measured at wavelengths of 260 nm. Quantitative analysis was performed at 285 nm.

[0046] Quantitative method: The amounts of substrate and oxidation product are calculated based on their respective external standard curves.

[0047] Combination Figure 1-3 Raman spectroscopy revealed characteristic D and G bands in the carbon material, corresponding to disordered / defective carbon and sp2-hybridized graphitic carbon, respectively. The high ID / IG ratio indicates a large number of structural defects in the carbon framework, which can provide anchoring sites for isolated cobalt atoms and contribute to the formation of a stable cobalt-nitrogen coordination structure. XRD results showed that the catalyst exhibited broad diffraction peaks corresponding to graphitic carbon (C002), while no obvious diffraction peaks corresponding to metallic Co, CoO, or Co3O4 were observed, indicating that the catalyst surface is mainly composed of single atoms. XPS results showed that the addition of nitrogen carbide resulted in a higher pyridine nitrogen ratio in the catalyst. This result indicates that the appropriate introduction of nitrogen carbide not only increases the total nitrogen loading but also modulates the nitrogen configuration within the carbon framework, thereby promoting the formation of pyridine N-type structures around Co-N4.

[0048] Catalytic experiments showed that the molar yield of 2,5-furandicarboxylic acid was 81.2%.

[0049] Examples 2-4

[0050] The corresponding catalysts were prepared according to the method of Example 1, except that in step (1), the mass of nitrogen carbide added was 0g, 2g, and 3g, respectively, and were denoted as Co-NC (1), Co-NC (3), and Co-NC (4). The catalysts prepared above were used to carry out the reaction according to the method of step (2) of Example 1. The detection results are listed in Table 1, with serial numbers 2, 3, and 4.

[0051] The Raman spectra of catalysts Co-NC(1), Co-NC(3), and Co-NC(4) are shown below. Figure 1 X-ray diffraction (XRD) patterns are shown below. Figure 2 The high-resolution N1s X-ray photoelectron spectroscopy (XPS) spectrum is shown below. Figure 3 .

[0052] Examples 2-4 investigated the effect of nitrogen carbide (g-C3N4) content on the catalyst structure, prepared Co-NC catalysts with different nitrogen carbide to carbon support mass ratios, and analyzed them using Raman spectroscopy, XRD, and XPS. Figure 1-3 Characterization was performed. Notably, regardless of the variation in the amount of nitrogen carbide added, no characteristic diffraction peaks of metallic Co, CoO, or Co3O4 were observed, indicating that cobalt was dispersed on the carbon support in single-atom form under different conditions without agglomeration. The increase in nitrogen carbide led to a higher proportion of pyridine nitrogen, which promoted the entire reaction.

[0053] Catalytic experiments showed that the molar yields of 2,5-furandicarboxylic acid were 55%, 85.5%, and 72%, respectively. The yield of the Co-NC(3) catalyst was not much different from that of the Co-NC(2) catalyst in Example 1. In comparison, the catalyst in Example 1 used less nitrogen carbide and had a higher single-atom mass, resulting in higher atom utilization.

[0054] Examples 5-6

[0055] The catalyst Co-NC(2) prepared in Example 1 was reacted according to step (2) of Example 1, except that the base neutralizing agents were calcium carbonate and magnesium oxide, respectively. The test results are listed in Table 1, numbered 5 and 6, respectively.

[0056] Catalytic experiments showed that the molar yields of 2,5-furandicarboxylic acid were 54.7% and 71.7%, respectively.

[0057] Examples 7-10

[0058] The catalyst prepared in Example 1 was used to carry out the reaction according to the method in Example 1, except that the catalytic reaction time was 1 h, 2 h, 4 h, and 5 h, respectively. The detection results are listed in Table 1, numbered 7, 8, 9, and 10, respectively.

[0059] Catalytic experiments showed that the molar yields of 2,5-furandiethanol were 27%, 56%, 78.5%, and 77.4%, respectively.

[0060] Examples 11-13

[0061] The catalyst prepared in Example 1 was reacted according to the method described in Example 1, except that the reactions were carried out at reaction temperatures of 110°C, 130°C, and 140°C for 3 hours, respectively. The test results are listed in Table 1, numbered 11, 12, and 13, respectively.

[0062] Catalytic experiments showed that the molar yields of 2,5-furandicarboxylic acid were 58.6%, 80.3%, and 79.5%, respectively.

[0063] Examples 14-15

[0064] The catalyst prepared in Example 1 was reacted according to the method described in Example 1, except that the reaction was carried out at 120°C for 3 hours under different oxygen pressures of 0.5 MPa and 2 MPa. The test results are listed in Table 1, numbered 14 and 15 respectively.

[0065] Catalytic experiments showed that the molar yields of 2,5-furandicarboxylic acid were 65.7% and 71.7%, respectively.

[0066] The results are summarized in Table 1 below:

[0067] Table 1. Effects of different catalyst types and process variables on the yield of 2,5-furandicarboxylic acid produced by the oxidation of 5-chloromethylfurfural.

[0068]

[0069] The results of the above specific embodiments demonstrate that the catalyst and alkali neutralizer provided by this invention can be effectively used for the hydrogenation of 5-chloromethylfurfural to prepare the high-value-added fine chemical 2,5-furandicarboxylic acid. The optimal catalytic reaction conditions are: reaction temperature 120℃, reaction time 3h, and oxygen pressure 1MPa.

[0070] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the protection scope of the present invention.

Claims

1. A method for preparing a carbon-doped N-supported single-atom cobalt catalyst, a Co-NC catalyst, characterized in that: Includes the following steps: (1) Dissolve cobalt acetate tetrahydrate and 1,10-phenanthroline in ethanol and stir until homogeneous; (2) Add the carbon support to the solution from step (1) and continue stirring; (3) Add nitrogen carbide to the mixture in step (2) and heat while stirring until the ethanol is completely evaporated; (4) Calcine the solid dried in step (3); (5) The black solid after calcination is acid-washed, water-washed and dried to obtain Co-NC catalyst.

2. The preparation method according to claim 1, characterized in that: The Co loading is 1-5%.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of cobalt acetate tetrahydrate to 1,10-phenanthroline is 1:1-1:5; preferably 1:1.5-1:2, and more preferably 1:1.75; in step (3), the mass ratio of nitrogen carbide to carbon support is 3:1-1:3, preferably 2:1-1:2, and more preferably 1:

1.

4. The preparation method according to claim 1, characterized in that: Step (1) The stirring time is 20-60 min, preferably 30 min; in step (2), the stirring time is 1-3 h, preferably 1 h; in step (3), the stirring is carried out at 50-90℃ until the ethanol is completely evaporated, preferably at 60-70℃; more preferably at 65℃; in step (4), the calcination is carried out at 700-1100℃ for 1-4 h, preferably at 900℃ for 2 h; in step (5), the calcined black solid is stirred in 6-10M H2SO4 for 10-36 h and then washed with water, dried and separated to finally obtain the Co-NC catalyst, preferably stirred in 8M H2SO4 for 24 h.

5. The Co-NC catalyst prepared by any one of claims 1-4.

6. The application of the Co-NC catalyst of claim 5, characterized in that, It was applied to the preparation of 2,5-furandicarboxylic acid from 5-chloromethylfurfural.

7. A method for preparing 2,5-furandicarboxylic acid using 5-chloromethylfurfural, characterized in that: The process includes the following steps: adding 5-chloromethylfurfural, the Co-NC catalyst of claim 5, an alkaline neutralizer, and water into a reaction vessel, using oxygen as the oxygen source, to catalyze the synthesis of 2,5-furandicarboxylic acid from 5-chloromethylfurfural.

8. The method as described in claim 7, characterized in that, The mass ratio of 5-chloromethylfurfural to Co-NC catalyst is 1:0.5-1:5; preferably 1:2; the mass ratio of 5-chloromethylfurfural to water is 1:30-1:250; preferably 1:50-100.

9. The method as described in claim 7, characterized in that, The mass ratio of 5-chloromethylfurfural to the alkali neutralizer is 1:1 to 1:3; preferably 1:2; the alkali neutralizer is one or more of calcium carbonate, magnesium oxide, and sodium bicarbonate; preferably sodium bicarbonate.

10. The method as described in claim 7, characterized in that, The initial oxygen pressure is 0.5-5 MPa, preferably 0.5-3 MPa, and more preferably 1 MPa; the reaction temperature is 100-150℃, preferably 110-130℃; the reaction is carried out at a stirring speed of 600-1000 rpm, preferably 800 rpm; the reaction time is 0.5-8 h, preferably 1-6 h, more preferably 2-5 h, and even more preferably 3 h.